Improvement of native grassland fields with use of lime and agricultural gypsum in “Campos de Cima da Serra”/RS (Revista de Ciências Agroveterinárias, 2021)
The objective of this work was to verify the effect of the application of lime in doses higher than those recommended and of agricultural gypsum on the productivity and macronutrient content of the native field in the "Campos de Cima da Serra" region (Southern Brazil). The experiment was conducted in a native pasture located in Vacaria municipality (Rio Grande do Sul state). The experiment was arranged in randomized blocks allocated in split plots, with four replications each. Conducted in a 3x2 factorial scheme: three doses of limestone (0, 3, and 5 ton ha-1, aiming to reach a base saturation of 65% and 5.0 ton ha-1, aiming to reach a base saturation 75%) and two doses of gypsum (0 and 2.0 ton ha-1), applied superficially. In addition, agricultural gypsum was randomly applied to one of the subplots. At the end of each climatic season, evaluations of forage mass production and macronutrient content were carried out in dry shoot matter in two samples collected from an area of 0.25 m2 per plot by cutting the aerial part "close to the ground”. The production of dry matter in the native field in autumn, winter and spring showed a significant increase with the application of 5 ton ha-1, with no influence in summer. Furthermore, the application of lime in the soil increased the nitrogen and potassium content in the leaf tissue of the native field in the autumn period. Interestingly, the same happens to calcium in the spring. On the other hand, the application of agricultural gypsum increased dry matter production only in spring and reduced magnesium contents in winter. Therefore, the results demonstrate the potential of using limestone in doses higher than those currently recommended and agricultural gypsum to increase natural forage production and their quality at time intervals evaluated in this work.
Keywords: liming; forage; nutrition